PREVALENCE OF GASTROPHILUS LARVAE IN DONKEYS - R. ALI, SAMI; Y. AL- KUBAISEE, RAFAA; H. RAHIF , RAAD (The Iraqi Journal of Veterinary Medicine, 2022)
The stomach, small and large intestine of 140 donkeys were examined for Gastrophilus larvae. The rate of infection was 45%, 6.4% and 7.8% for Gastrophilus intestinalis, G. nasalis G. pecorum, respectively, with the mean larval counts of 3rd instars; 25.8, 10.4 and 27.7, for the respective species. Excepting the month October, third instars of G. intestinalis were found throughout the year. The peak of infection (87.5%) was recorded in February, while the lowest rate (7.1%) was in November. This rate and mean larval burden seemed to decline with the age of the host. The sex of the animals had no effect on the rate of infection. G. pecorum, and G. nasalis are reported for the first time in Iraq and occurred only during the months of June, August and September.